2011
DOI: 10.1002/ajp.20959
|View full text |Cite
|
Sign up to set email alerts
|

Aggression, grooming and group‐level cooperation in white‐faced capuchins (Cebus capucinus): insights from social networks

Abstract: The form of animal social systems depends on the nature of agonistic and affiliative interactions. Social network theory provides tools for characterizing social structure that go beyond simple dyadic interactions and consider the group as a whole. We show three groups of capuchin monkeys from Barro Colorado Island, Panama, where there are strong connections between key aspects of aggression, grooming, and proximity networks, and, at least among females, those who incur risk to defend their group have particul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 59 publications
(56 reference statements)
2
35
0
1
Order By: Relevance
“…On the other hand, only a small proportion of possible agonistic interactions were observed in the growing and the breeding stables. This sparseness of agonistic interaction networks was also seen in other studies (Crofoot et al, 2011). Beside the larger group and pens sizes, another possible reason for these findings could be a habituation effect in growing pigs and gilts due to the repeated rehousing and mixing situations.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…On the other hand, only a small proportion of possible agonistic interactions were observed in the growing and the breeding stables. This sparseness of agonistic interaction networks was also seen in other studies (Crofoot et al, 2011). Beside the larger group and pens sizes, another possible reason for these findings could be a habituation effect in growing pigs and gilts due to the repeated rehousing and mixing situations.…”
Section: Discussionsupporting
confidence: 56%
“…As the results illustrate, these cycles included on average more than two animals, which suggests that agonistic interactions have a group-wide structure which is not immediately obvious in a dyadic analysis (Crofoot et al, 2011). Indeed, the strongly connected components included about 90% of the animals in weaned pigs, 70% in growing pigs and 60 % in gilts, indicating that these animals were involved in mutual agonistic interactions.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…To cope with this challenge, many researchers adopt social network analysis, an analytical tool of increasing importance in the study of animal behavior (Wey et al 2008; Brent et al 2011), which uses complex algorithms to visualise and quantify social structure topology (Croft et al 2008). Social network-based studies have examined, for example, whether topologies differ between species (Maryanski 1987; Sundaresan et al 2007; Kasper and Voelkl 2009; Sueur et al 2011), or between groups of the same species (Hanby 1980; Godfrey et al 2009; Madden et al 2009; Crofoot et al 2011), and have demonstrated that social structures often exhibit certain fundamental topological properties (e.g. small-world properties: Lusseau 2003; Croft et al 2005; Sundaresan et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The inclusion of additional parameters such as the risk of infanticide and habitat saturation have created expanded socioecological models that can predict female grouping in gorillas and lions, and the formation of ‘friendships’ in chacma baboons ( Papio cynocephalus ursinus ) [15]–[19]. Within a social group, age, sex, social status, and hunger level can greatly influence an individual's choice of whom to interact with and in what manner [20][24]. Some species exhibit age-based homophily, in which individuals preferentially interact with conspecifics of the same age, regardless of relatedness [25].…”
Section: Introductionmentioning
confidence: 99%